Show me the money and I will bring you the head: evaluation of the effects of self-interest and anger on whistleblowing - Lagowska, Urszula Gabriela (2016)
Though many of those who decided to report wrongdoings in their organizations were able to tell their stories (e.g. Bamford, 2014, Armenakis 2004), it is fair to say that there is still much left to uncover. The paper aims to contribute to the literature in three ways. First, it provides preliminary evidence that the wrongdoing linked with individual financial loss leads to higher whistleblowing rate. Secondly, it shows how the experience of anger is related to the higher likelihood to report the wrongdoer but only if the wrongful act is perceived as a cause of one’s financial loss. Finally, the paper establishes first steps for the future development of an experimental procedure that would enable to predict, and measure whistleblowing behavior in the lab environment.